2023
DOI: 10.1177/21582440231217902
|View full text |Cite
|
Sign up to set email alerts
|

Factor Influencing the Adoption of Big Data Analytics: A Systematic Literature and Experts Review

Showimy Aldossari,
Umi Asma’ Mokhtar,
Ahmad Tarmizi Abdul Ghani

Abstract: In the current market landscape, enterprises face tremendous pressure to remain competitive and innovative to extend their businesses globally. Thus, a need exists for a new data analysis technique and a tool known as Big Data Analytics (BDA), which refers to massive data sets in light of their volume, velocity, variety, and veracity. Small and Medium Enterprises (SMEs) face challenges in obtaining and utilizing the knowledge derived from big data to make informed decisions regarding market selection and adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 110 publications
0
6
0
1
Order By: Relevance
“…"Mobile learning and students", S5= "Mobile learning in education" S1= "399", S2= "53", S3= "39", S4= "6", S5= "10" The detailed methodology of this study is not just a procedural backbone but a critical element that directly shapes the credibility, specificity, and applicability of our findings and conclusions. This kind of study allows us to confidently assert that the identified critical success factors are key influencers in the effective implementation and perceived impacts [32] of mobile learning in students' education. The following sub-sections explain the SLR steps in detail.…”
Section: Systematic Literature Review (Slr) Methodologymentioning
confidence: 98%
See 4 more Smart Citations
“…"Mobile learning and students", S5= "Mobile learning in education" S1= "399", S2= "53", S3= "39", S4= "6", S5= "10" The detailed methodology of this study is not just a procedural backbone but a critical element that directly shapes the credibility, specificity, and applicability of our findings and conclusions. This kind of study allows us to confidently assert that the identified critical success factors are key influencers in the effective implementation and perceived impacts [32] of mobile learning in students' education. The following sub-sections explain the SLR steps in detail.…”
Section: Systematic Literature Review (Slr) Methodologymentioning
confidence: 98%
“…This study adopted the SLR based on a comprehensive and systematic method for identifying and analyzing the studies [31][32][33] in M-learning adoption among students of higher education institutions. The steps taken towards carrying out the SLR are presented in the following Fig.…”
Section: Systematic Literature Review (Slr) Methodologymentioning
confidence: 99%
See 3 more Smart Citations